2017
DOI: 10.1039/c7ra00632b
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur doped graphene as a promising metal-free electrocatalyst for oxygen reduction reaction: a DFT-D study

Abstract: As an efficient metal-free catalyst, graphene doped with heteroatoms is highly active in promoting electrochemical oxygen reduction reaction (ORR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 42 publications
7
28
0
Order By: Relevance
“…First-principles calculations within the density functional theory (DFT) methods were carried out in the Vienna ab initio simulation package (VASP). [36][37][38] The PBE methods have been employed to investigate the structural stability and electronic properties, and the HSE hybrid functional methods have been used to check the band gaps of all the cases employed here to overcome the problem of band gap underestimation in PBE functional. 39,40 The projector augmented wave (PAW) method is used to describe the electron-ion interaction, and the valence electrons of 4s 2 4p 2 for Sn and 3s 2 3p 4 for S atoms have been adopted in the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…First-principles calculations within the density functional theory (DFT) methods were carried out in the Vienna ab initio simulation package (VASP). [36][37][38] The PBE methods have been employed to investigate the structural stability and electronic properties, and the HSE hybrid functional methods have been used to check the band gaps of all the cases employed here to overcome the problem of band gap underestimation in PBE functional. 39,40 The projector augmented wave (PAW) method is used to describe the electron-ion interaction, and the valence electrons of 4s 2 4p 2 for Sn and 3s 2 3p 4 for S atoms have been adopted in the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…[271,338] Moreover, the abundant states near the Fermi level may indicate the high activity of the catalysts. [339] For instance, Lu et al [340] investigated the sulfurdoped graphene for ORR by the DOS analysis. As shown in Figure 9a, the emerged peaks in the DOS profile mainly come from the sulfur dopant and its neighboring C atom, indicating that the enhanced activity stemmed from Sdoping.…”
Section: Density Of Statesmentioning
confidence: 99%
“…[377] By comparing the barrier heights for different reaction pathways, one can find the mechanism of the electrocatalytic reaction. [378][379][380][381] Taking the formation of *O and *OH on S-doped graphene as example (Figure 9g), [340] DFT calculations have shown that the first step is the co-adsorption of *O 2 and *H. Subsequently, the *H moieties approached *O 2 to form the metastable state of *OOH on the S site. Afterward, the adsorbed *OOH is dissociated into co-adsorption of *O + *OH species and they move to a proper site to form the most stable configuration.…”
Section: Transition State Theory (Tst)mentioning
confidence: 99%
See 1 more Smart Citation
“…Technically, precious Pt-based nanomaterials are the commercial electrocatalysts for the oxygen reduction reaction (ORR), which reports 36-56% of the cost of the PEMFCs [188]. Various heteroatomdoped carbon materials [189], sulfur-doped graphene (SG) [190], phosphorous-doped graphite layers [191], iodine-doped graphene [192] and edge-halogenated (Cl, Br, or I) graphene nanoplatelets [193] and mesoporous nitrogen-doped carbons prepared from ionic liquids and nucleobases for productive metal-free oxygen reductions [194] are investigated. An article published by Iqbal et al [195] outlines graphene-based materials for fuel cell technology applications such as electrodes additives, bipolar plates and proton conducting electrolyte membrane.…”
Section: Go/rgo As Electrocatalystmentioning
confidence: 99%